EMOTIONAL IMPACT OF JAMES BOND SERIES TRAILERS: NARRATIVE AND CINEMATIC TECHNIQUES - Лукьянец, Татьяна (SWorldJournal, 2021)
This paper examines James Bond series trailers regarding their capability of having significant emotional effect on viewers. Emotivity of this cinematographic sub-genre has been studied from a lingual and cinematic perspective taking into account psychol